Positive correlation between psoriasis vulgaris severity degree with HbA1C level - Made Swastika Adiguna; Made Wardhana; Fresa Nathania Rahardjo (Bali Dermatology and Venereology Journal, 2018)
Introduction: Psoriasis is a skin abnormality based on chronic inflammation immune mediated. Inflammatory mediator roles (Th-1, TNF-α, IL-6,IL-7, IL-8, IL-17, and IL-23) in its pathogenesis proven to inhibit insulin receptor and glucose uptake from fat tissue and causing insulin resistance, then blood glucose level increased. Mean blood glucose level within 3 months can be represented by HbA1c (glycosylated haemoglobin) level. HbA1c is a bond between glucose and hemoglobin.           Objective: The aim of this study is to understanding correlation between psoriasis vulgaris severity degree with HbA1c.Material and methods: This study is using cross sectional method. HbA1c level examination done by drawing venous blood, then analyzed with chromatography method. Samples were selected by using inclusion and exclusion criteria and consecutive sampling method.Result: Study result shows subject consist of total 51 subjects consists of 33 subjects with psoriasis vulgaris (22 males and 11 females with youngest age of 15 and oldest age of 65 years old), and 18 subjects without psoriasis vulgaris. Psoriasis vulgaris severity degree measured with Psoriasis Area Severity Index (PASI), then grouped to 3 categories: mild PASI score <6, moderate PASI score  6 – 12, and severe PASI score> 12. Mostly  (15 subjects) including mild category. HbA1c level on this study subjects resulted minimum level of 4.6%, maximum 12.1 %, and median 5.4%.  Based on Perkeni consensus, normal HbA1c level is <5,7%, prediabetes 5,7-6,4%, and diabetes >6,5%. HbA1c level of psoriasis vulgaris subjects are higher than non psoriasis vulgaris subjects significantly (p=0,019). Psoriasis vulgaris causing increase of HbA1c level with Prevalence Ratio (PR) 6,55. Thus, Psoriasis vulgaris subjects have increased risk 6,5 times to increase HbA1c level compared with non psoriasis vulgaris subjects. Correlation between severity degree and HbA1c level found in positive course significantly with moderate strength of correlation (Spearman correlation; r = 0.580, p<0,001).Conclusion: HbA1c level on psoriasis vulgaris subjects are higher than non psoriasis vulgaris, and psoriasis vulgaris severity degree positively correlated with HbA1c increasing level. Every increase of  psoriasis vulgaris severity degree will cause increase level of  HbA1c.